Possibilidades e limites de uma intervenção pedagógica pautada na metodologia da sala de aula invertida para os anos finais do ensino fundamental - Almeida, Braian Lucas Camargo (2017)
This research presents the results of the investigation about the possibilities and limits of the use of the Inverted Classroom methodology in mathematics classes for final grades of Elementary School, specifically the 8th grade, through the production and application of a proposal based on this methodological resource. In this teaching approach, also known as Flipped Classroom, the student has contact with the basic information about the study content before class. Thus, it extends the time of the school space for practical activities of understanding and solving problems and for the personalized attendance of the student. The research was justified due to the shortage of works related to the inverted classroom, at national level, mainly in the teaching of Mathematics in Elementary School and High School. Through the perceptions of the parents, students, pedagogical team and the researcher teacher, we sought to investigate the possibilities and limits that the inverted classroom methodology, adapted in a proposal and the reality of the teacher, would be more evident. These results were obtained from questionnaires, recordings of meetings, record sheets, annotations and reports, and were submitted to content analysis, according of Bardin (2006), which made it possible to identify the expressed understandings by the participants of this study. The study which had a qualitative character started from the literature review to identify the state of the art on the subject. After this stage, there was a need to elaborate a Proposal for the Application of the Inverted Classroom (PASAI), where such methodology was made active, adaptation to the reality of the researcher professor and contents of equations of the 1st grade, inequalities of the first degree and systems of equations of the first degree with two unknowns. The PASAI is based on the steps: motivation; online material; resolution and presentation of tasks; problem solving and task diversification, in which each of them has strategies that allow the flipped classroom to be applied. Among the possibilities found in this application, we highlight students’ participation and interest; the use of video classes; collaborative learning and better understanding of content through task presentations. Already regarding the limits, we evidenced the lack of maturity of some students; the short class time for some steps and the lack of adaptation of the students in relation to weekly online work as a form of evaluation. In addition, it was interesting to note that the PASAI shows potential adaptability to other mathematical contents, different from those used during an application of the proposal, due to its diversified stages and facility inclusion of them the reality of the teacher who can adopt this proposal. We hope that the possibilities and limits found in this research will be useful for future applications of this methodology in the classroom.